Tuberculous Spondylitis : A Case Report - Stefany Palyama; Retno Wisanti; Rusdian Niati Ningsih (The International Journal of Medical Science and Health Research, 2025)
Objective: Tuberculous spondylitis is an infection of the spine caused by the Mycobacterium tuberculosis , is one of the most common infections. The WHO reports that 10.6 million TB cases are worldwide by 2022. By 2022, TB is the disease that causes the most deaths, with 1.3 million per year. Spondylitis Tuberculosis was extra pulmonary TB. The symptoms are fever, sweating especially at night, weight loss and loss of appetite, and palpable mass on the back. The sass can lead to permanent neurological deficits. The early identification and treatment is very important to avoid permanent damage in the future. Case: A 4 years old female patient with complaints of disappearing pain in the back since 10 days. A fever that has persisted for ten days and sweating at night. The patient's weight also decreased by 6kg. Immunization history is incomplete. There are no BCG vaccines. Her uncle had TB from 2018 and her neighbors too. Impression nutritional status was undernourished. Enlargement of the lymph in the neck area, and rhonci sounds in both fields of the lung were observed during the physical examination of the thorax. Tuberculin test showed induration 10mm. There was fixed palpable mass at the back, hard, no fluctuations, no rebound tenderness. Lumbosacral examination without contrast revealed a mass between vertebrathoracal ( VTh ) 4-9, it showed cold abscess. Lumbosacral MRI revealed compression anterior of the veterbralthoracal corpus ( VTh ) 7, and pushing to the spinal cord posteriorly, and showed gybus formation, and abscess on the anterior of veterbralthoracal ( VTh 4-7). Based on the patient's medical history, physical examination, laboratory, the patient was diagnosed with TB spondylitis. The patient underwent spinal stabilization and decompression, in addition to receiving OAT treatment. Conclusion: TB spondylitis is a rare case in children, but it is common in children with primary TB infection. Systemic and neurological symptoms can be found in patients with TB Spondylitis . The prognosis of TB Spondylitis is influenced by the age of the patient, the severity of bone deformity, the number of spinal bone involvement, and the patient's health history such as immunization status, nutritional status, and other accompanying diseases.